2020
DOI: 10.3389/fmicb.2020.603481
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Storage Conditions on the Quality, Metabolites, and Biological Activity of Soursop (Annona muricata. L.) Kombucha

Abstract: Kombucha is a slightly alcoholic beverage produced using sugared tea via fermentation using the symbiotic culture of bacteria and yeast (SCOBY). This study aimed to optimize the production of soursop kombucha and determine the effects of different storage conditions on the quality, metabolites, and biological activity. The response surface method (RSM) results demonstrated that the optimum production parameters were 300 ml soursop juice, 700 ml black tea, and 150 g sugar and 14 days fermentation at 28°C. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 36 publications
3
14
0
1
Order By: Relevance
“…On the other hand, kombucha is an ancient beverage made from sugared tea using symbiotic culture of bacteria and yeast (SCOBY) ( Chakravorty et al, 2016 ). It is health benefits include antioxidant ( Muhialdin et al, 2019 ), anticancer ( Villarreal-Soto et al, 2019 ), antimicrobial ( Tan, Muhialdin, & Meor Hussin, 2020 ), Plant-based fermented foods and beverages are regularly consumed in Asia and Africa with less frequent at the Western countries where milk-based fermented foods are dominant ( Tamang et al, 2020 ). However, the increased awareness regarding their health benefits alongside the recent Covid-19 pandemic have led to increase the demand for the plant-based fermented foods and beverages ( Antunes, Vinderola, Xavier-Santos, & Sivieri, 2020 ).…”
Section: Fermented Foodsmentioning
confidence: 99%
“…On the other hand, kombucha is an ancient beverage made from sugared tea using symbiotic culture of bacteria and yeast (SCOBY) ( Chakravorty et al, 2016 ). It is health benefits include antioxidant ( Muhialdin et al, 2019 ), anticancer ( Villarreal-Soto et al, 2019 ), antimicrobial ( Tan, Muhialdin, & Meor Hussin, 2020 ), Plant-based fermented foods and beverages are regularly consumed in Asia and Africa with less frequent at the Western countries where milk-based fermented foods are dominant ( Tamang et al, 2020 ). However, the increased awareness regarding their health benefits alongside the recent Covid-19 pandemic have led to increase the demand for the plant-based fermented foods and beverages ( Antunes, Vinderola, Xavier-Santos, & Sivieri, 2020 ).…”
Section: Fermented Foodsmentioning
confidence: 99%
“…Fresh and ripen soursop (Annona muricata L.) fruits High potential to improve the quality, metabolites content, biological activity, and the Halal status of soursop kombucha [103] Black tea + sugar Invertase in kombucha tea increase the nutritional value of fermented product for diabetes patients [104] Green/black tea + guava juice Antimicrobial activity against human pathogenic bacterial strains and pathogenic fungi [105] Lactose and lactose-free milk Due to active microflora and organic acids, have a confirmed positive effect on the human body [106] Jujube kernel Obtaining of functional beverages and jujuboside B [107] Unbleached wheat flour Encapsulated kombucha-like sourdough starter for production of functional sourdough bread with extended shelf life and improved quality [108] Back tea with total replacement or in combination with Melissa officinalis, Quercus robur, Vaccinium myrtillus, Callisia fragrans Ascorbic acid and rutin obtaining [109] Probiotic bacteria from milk kefir grains use the carbon-and nitrogen-based nutrients within the fermentation medium and produce metabolites such as organic acids or carbonyl compounds and esters. In this way, products with specific taste and aroma are obtained.…”
Section: Kombuchamentioning
confidence: 99%
“…Recently, in order to reduce the heavy burden of foodborne diseases, natural antiseptic strategies have been increasingly developed to control foodborne pathogens (Ghazy et al, 2021;Kim et al, 2021;Savas et al, 2020;Zhu et al, 2021). Kombucha is known as anacidic and sweet refreshing beverage obtained from fermented sugared tea (Cardoso et al, 2020) or other substrates such as grape juice (Ayed et al, 2017), soursop (Tan et al, 2020), yarrow (Vitas et al, 2018), coffee (Bueno et al, 2021), and milk (Kruk et al, 2021). This fermentation is carried out by a characteristic consortium of yeasts, acetic acid bacteria, and often, but not always, lactic acid bacteria (Figure 1) (Coelho et al, 2020).…”
Section: Microbiological Composition Of Kombuchamentioning
confidence: 99%
“…Moreover, the antibacterial activity of heat-denatured kombucha indicates that this thermo-stable antimicrobial agent could be used in food products to control thermophilic spore-forming bacteria (Kaewkod et al, 2019). Tan et al (2020) proved that acetic acid in kombucha could penetrate Gram-positive bacteria cells more easily than Gram-negative bacteria because of its lipophilic characteristics, and the highest proportion of microbial growth inhibition against E. coli and S. aureus was 99.83% and 100%, respectively. However, Sreeramulu et al (2000) confirmed the presence of antimicrobial compounds in fermentative ability to hydrolyze sucrose into fructose and glucose by action of invertase, followed by the generation of ethanol via glycolytic pathway.…”
Section: Acidsmentioning
confidence: 99%